PRODUCTION OF ACCURATE EQUIPMENT, ACCELERATION OF PREPRODUCTION AT DEVELOPMENT OF NEW FOUNDRY OUTPUT - A. P. Melnikov; M. A. Sadoha; D. M. Golub; N. A. Yatsevich (Литьë и металлургия)
The scheme of the development and establishment of tooling foundry technology for a wide range of products made of steel, cast iron, non-ferrous metals and alloys is studied.